Religious Practice and the Claims of Anthropology - Webb Keane (Suomen Antropologi, 2008)
It is an enormous honor to be here to celebrate the memory of Edvard Westermarck. A Swedish-speaking Finn, a Scandinavian emissary to London, a Northerner intimate with Morocco, a founding figure across the emergent disciplinary boundaries between sociology and anthropology, Westermarck was a cosmopolitan in the best sense of the word. From his position betwixt and between, he was well placed to identify the two central challenges of relativity that have long marked the human sciences in general, and anthropology in particular. One is ontological, the other moral. From the start, given their vast ambition to understand humans in the broadest social context, anthropologists have frequently had to grapple with reality claims and ethical norms far from their own. To his enduring credit, Westermarck had the courage to face the problem directly, and early on staked out one of the more radical and still unsettled positions on the relativistic implications of anthropology. In a world of ever faster and more widely circulating people, images, and ideas, the challenges posed by other reality claims and other moral values have only become more pressing.